Aposematism in the burying beetle? Dual function of anal fluid in parental care and chemical defense. (22nd August 2017) - Lindstedt, Carita; Boncoraglio, Giuseppe; Cotter, Sheena; Gilbert, James; Kilner, Rebecca M
Abstract : Versatility of anal fluid in burying beetles? Burying beetles use the same anal fluid to fumigate their carrion nest and to deter predators. The orange-black markings on beetle's elytra are conspicuous for birds and could function as a warning signal of these defensive chemicals. The markings and volume of fluid are highly variable and females produce more fluid than males, so might be better at teaching birds to avoid prey with similar markings. Abstract: Burying beetles ( Nicrophorus vespilloides ) bear distinctive and variable orange-black patterning on their elytra and produce an anal exudate from their abdomen when threatened. During breeding, the anal exudates contribute to the antimicrobial defense of the breeding resource. We investigated whether the anal exudates also provide a responsive chemical defense, which is advertised to potential avian predators by the beetle's orange and black elytral markings. We found that that the orange-black elytral markings of the burying beetle are highly conspicuous for avian predators against range of backgrounds, by using computer simulations. Using bioassays with wood ants, we also showed that the burying beetle's anal exudates are aversive to potential predators. From these results, and other evidence in the literature, we conclude that the evidence for aposematism in the burying beetle is as strong as the evidence for many other classically aposematic species, such as defended Hymenopterans, ladybirds, or poisonous frogs. Nevertheless, we also report unexpectedly high levels of individual variation in coloration and chemical defenses, as well as sex differences. We suggest that this variation might be partly due to conflicting selection pressures, particularly on the dual function of the exudates, and partly to nutritional differences in the developmental environment. The ecology of the burying beetles ( Nicrophorus spp.) differs markedly from better-studied aposematic insects. This genus thus offers new potential for understanding the evolution of aposematism in general.